Model Penanganan Dan Pencegahan Pelecehan Seksual Pada Lingkungan Universitas Di Kota Pekanbaru - Elmayanti yanti Elmayanti; Davit Davit Rahmadan; Erdiansyah Erdiansyah (Fakultas Hukum Universitas Riau, 2023)
There are thousands of victims every year, and Komnas Perempuan reports that in 2020 alone there were around 8,000 cases that went unreported. Around 5,000 of them were carried out by the perpetrators who were supposed to protect the victims, such as fathers, brothers, uncles (incest), as well as school teachers, religious teachers, lecturers, and the police. With the Minister of Education and Culture Regulation (Permendikbud) Number 30 of 2021 which aims to protect students from sexual violence. The condition of zero tolerance for sexual violence on campus, which was initiated by the Minister of Education and Culture, is highly anticipated. In 2019, there were 174 cases in 79 campuses in 29 provinces. The objectives of this research are; First, to provide physical and psychological protection for victims of sexual violence that occurred in the university environment, especially in Pekanbaru. Second, to provide solutions in handling cases of sexual violence, both penal and non-penal. Third, to provide prevention and education about sexual violence in the university environment, especially in the city of Pekanbaru.